Recycling cell formation using group technology for disposal products - Park, J.H.; Seo, K.K.; Jang, D.S. (Proceedings - 1st International Symposium on Environmentally Conscious Design and Inverse Manufacturing, EcoDesign 1999, 1999)
The recycling cell formation problem means that disposal products are classified into recycling part families using group technology in their end of life phase. Disposal products have the uncertainties of product status by usage influences. Recycling cells are formed considering design, process and usage attributes. In this paper, a novel approach to the design of a cellular recycling system is proposed, which deals with the recycling cell formation and assignment of identical products concurrently. Fuzzy clustering and fuzzy-ART algorithms are applied to describe the states of disposal product with the membership functions and to make recycling cell formation. This approach leads to recycling and reuse of the materials, components, and subassemblies and can evaluate the value at each cell of disposal products. Application examples are illustrated by disposal refrigerators, comparing fuzzy clustering with fuzzy-ART performance in cell formation. ？ 1999 IEEE.